997Childhood pneumonia in the Eastern Highlands Province, Papua New Guinea: clinical predictors of severe disease. (2nd September 2021) - Britton, Kathryn; Pomat, William; Ford, Rebecca; Sapura, Joycelyn; Kave, John; Nivio, Birunu; Lehmann, Clinical Deborah; Chan, Jocelyn; Russell, Fiona; Blyth, Clinical Christopher
Abstract: Background: Pneumonia is the leading cause of death in young children globally and is prevalent in the highlands of Papua New Guinea (PNG). We investigated clinical predictors of severe pneumonia to inform local treatment guidelines in this resource-limited setting. Methods: Between 2013 and 2020, prospective studies were undertaken enrolling children <5 years presenting with pneumonia to health-care facilities in Goroka Town, Eastern Highlands Province. Physical examination findings and blood cultures were collected. Logistic regression analyses were performed to determine predictors of hypoxaemia (oxygen saturation <90% on presentation), bacteraemia and death. Results: There were 2067 cases of pneumonia, hypoxaemia was detected in 36.1%. Bacteraemia was identified in 47/1943 (2.4%) blood cultures. Of 1444 children followed up, 18 (1.2%) died. Central cyanosis (odds ratio 3.82, 95% CI 2.55-5.71) and reduced breath sounds (2.77, 2.17-3.53) independently predicted hypoxaemia; altered consciousness (21.44, 3.91-117.48), bronchial breathing (10.49, 2.01-54.63) and apnoea (2.54, 1.26-5.14) independently predicted bacteraemia; and altered consciousness (20.95, 2.32-189.00), reduced skin turgor (14.43 (4.79-43.49) and central cyanosis (5.96, 2.13-16.66) independently predicted death. Conclusions: In children with pneumonia in the PNG highlands, those with central cyanosis, apnoea, bronchial breathing, altered consciousness or reduced skin turgor are at greatest risk of severe outcomes. Ongoing training of health care workers is essential to ensure these signs are recognised and appropriate management promptly instituted. Key messages: Prompt recognition of signs of severity is likely to lead to better outcomes for children in PNG with pneumonia. These findings will inform future modifications to local treatment guidelines.